Using Student Performance Data to Identify Effective Classroom Practices - Tyler, John H; Taylor, Eric S; Kane, Thomas J; Wooten, Amy L (American Economic Review, 2010)
Using Student Performance Data to Identify Effective Classroom Practices by John H. Tyler, Eric S. Taylor, Thomas J. Kane and Amy L. Wooten. Published in volume 100, issue 2, pages 256-60 of American Economic Review, May 2010